2022
DOI: 10.3390/cimb44020054
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Two Genes Encoding Novel Ca2+-Independent Phospholipase A2s from the Silkworm, Bombyx mori

Abstract: Eicosanoids are crucial downstream signals in the insect immune responses. Phospholipase A2 (PLA2) catalyzes phospholipids, the initial step in eicosanoid biosynthesis. In mammals, the biological roles of Ca2+-independent Phospholipase A2 (iPLA2) have been extensively studied; however, only a few studies have attempted to explore iPLA2 functions in insects. In this study, we identified two iPLA2 genes (designated as BmiPLA2A and BmiPLA2B) in the silkworm, Bombyx mori. BmiPLA2A had a 2427 base pair (bp) open re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Previous studies have also documented that pathogen stimuli significantly affect iPLA2 family members' expression levels. 15,42 It has also been demonstrated that iPLA2 isoforms exhibit lipid hydrolase or transacylase/ acyltransferase activities. 23 The lack of F I G U R E 1 1 Phylogenetic tree of deduced amino acid sequences for PLA2 family members from A. crassicauda.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also documented that pathogen stimuli significantly affect iPLA2 family members' expression levels. 15,42 It has also been demonstrated that iPLA2 isoforms exhibit lipid hydrolase or transacylase/ acyltransferase activities. 23 The lack of F I G U R E 1 1 Phylogenetic tree of deduced amino acid sequences for PLA2 family members from A. crassicauda.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that PLA2s play their roles by producing lipid mediators, altering membrane phospholipid composition, degrading foreign phospholipids, and modifying extracellular lipid components such as lipoproteins. [13][14][15][16] The catalytic activity of the PLA2s triggers a cascade of inflammatory events including release of a complex network of inflammatory mediators. 17,19 The existing literature demonstrates that the sPLA2 subfamily catalyzes the hydrolysis of the sn-2 fatty acid bond of phospholipids, releasing free fatty acids and lysophospholipids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that in order for the host to respond effectively to microbial pathogens, a number of cellular signals require to be finely modulated, including immune signaling (3,(96)(97)(98). As described above, miRNA expression is strongly altered in response to bacterial pathogens.…”
Section: Immune Signaling Is Affected By Mirna Fluctuation During Bac...mentioning
confidence: 99%
“…There are significant medical and economic costs associated with viruses that infect insects. So far, a large number of studies and review articles have been published that address the insect innate immunity and the molecules associated with immunity that is involved in the anti-viral processes of insects [ 73 , 74 , 75 , 76 , 77 , 78 ]. However, the biological role of circRNAs in the regulation of innate immunity during viral infection is still unknown.…”
Section: Circrnas In the Innate Immunity Of Insectsmentioning
confidence: 99%